PTH-023 Developing patient reported experience measures for gi endoscopy: results of patient interviews. (17th June 2017) - Neilson, LJ; Sharp, L; Patterson, J; Hewitson, P; Wagner, Cvon; Rees, CJ
Abstract : Introduction: Patient experience is increasingly recognised as a key measure of quality of care. Ensuring positive experience is important to patients and fundamental in maximising participation in screening programmes and re-attendance for surveillance procedures. Current measures of patient experience of gastrointestinal (GI) endoscopy are clinician derived. 1 Patient Reported Experience Measures (PREMs) should be patient derived and incorporate pre-and post-procedure experience. We aimed to identify themes considered as important to patients undergoing GI procedures as a basis for developing PREMs. Method: Patients who had undergone upper or lower GI investigations (gastroscopy, colonoscopy and CT pneumocolon) were invited to attend for a semi-structured interview. 32 interviewees were purposefully sampled to ensure diversity. Interviews were conducted by a research fellow trained in qualitative methods and were audio recorded and transcribed verbatim. Recruitment continued until saturation was achieved. Analysis used qualitative thematic methods focusing on anticipated and emergent themes, using constant comparison to ensure that all perspectives were included in the explanation of the data. Results: 168 patients were approached. 32 interviews were completed (12 gastroscopy, 10 colonoscopy and 10 CT pneumocolon), with a male:female ratio of 18:14. The time interval from examination to procedure ranged from 5 to 44 days. Mean age was 63.1 years (SD 11.5) The interviews provided an in-depth understanding of patient experience of GI procedures. 6 over-arching and inter-linking themes emerged across all procedures; anxiety, expectations, choice/control, communication/information, comfort and embarrassment/dignity. Relation of themes was seen e.g. if the procedure appointment was sooner than expected, patients were anxious about the potential outcome. Choice was important in terms of appointment, endoscopist and choice of pre-medication, however it was highly individualised. Communication prepared patients and managed expectations, with one patient describing poor endoscopist communication affecting the whole experience. Patients described embarrassment related to changing and waiting areas; sensitive nature of the test; exposure and physical reaction. Discomfort during the procedure was attributed to instrument and air insertion. Conclusion: Despite heterogeneity between procedures consistent themes related to patient experience emerged. This work will be used to develop PREMs for GI Endoscopy. Reference: . Brown S, et al. Patient-derived measures of GI endoscopy: a meta-narrative review of the literature. Gastrointest Endosc2015;81(5):1130–40 Disclosure of Interest: None Declared